UJI AKTIVITAS ANTIFUNGI EKSTRAK DAUN KEMANGI (Ocimum basilicum L.) TERHADAP DAYA HAMBAT Candida albicans SECARA IN VITRO PADA KANDIDIASIS VULVOVAGINALIS - Funsu Andiarna; Mei Lina Fitri Kumalasari; Moch. Irfan Hadi (Fakultas Biologi | Universitas Jenderal Soedirman, 2023)
Basil (Ocimum basilicum L.) can be used as a treatment for vulvovaginal candidiasis because it contains essential oils where there are flavonoids, alkaloids, tannins and saponins which can inhibit growth and kill fungal cells of Candida albicans. The purpose of this study was to determine the antifungal activity of basil leaf extract (O. basilicum) with variations in the concentration of the solution to the inhibition of C. albicans in vitro in vulvovaginal candidiasis. This study was an experimental study with basil leaf extract samples with various concentrations of 6.25 mg / ml; 12.5 mg / ml; 25 mg / ml; 50 mg / ml; 100 mg / ml; control (+) by giving 2% ketoconazole and control (-) by giving 10% DMSO. The research method uses disc diffusion test. Phytochemical tests of basil leaves showed that the leaves contained flavonoids, alkaloids, tannins, and saponins positively. The inhibition of C. albicans is best in the extract of O. basilicum leaves with a concentration of 100 mg/ml. The greater the concentration of the extract given, the more inhibited power will be formed because the concentration of the bioactive components contained in the extract is higher. Key Words: Basil leaf extract, Candida albicans, Inhibitory power, Antifungal compounds